Japan and the Great Divergence, 730-1874 - Bassino, J; Broadberry, S; Fukao, K; Gupta, B; Takashima, M (Elsevier, 2018)
Despite being the first Asian economy to achieve modern economic growth, Japan has received relatively little attention in the Great Divergence debate. New estimates suggest that although the level of GDP per capita remained below the level of northwest Europe throughout the period 730-1874, Japan experienced positive trend growth before 1868, in contrast to the negative trend growth experienced in China and India, leading to a Little Divergence within Asia. However, growth in Japan remained slower than in northwest Europe so that Japan continued to fall behind until after the institutional reforms of the early Meiji period. The Great Divergence thus occurred as the most dynamic part of Asia fell behind the most dynamic part of Europe.